Management of cancer patients during the COVID-19 pandemic: A narrative review - Alfredo Tartarone; Marina Tartarone (临床与病理杂志; 卷 41, 编号 8 (8 2021), 2021)
Objective: We wrote this review with the objective of helping the physicians to manage patients with cancer during the COVID-19 pandemic. Background: In the absence of specific curative treatments, COVID-19 exerted worldwide a dramatic impact on public health and socio-economic aspects. Patients with cancer represent a vulnerable population when suffering from COVID-19 infection since they usually present a series of risk factors such as immunosuppressed state, older age, comorbidities (e.g., cardiovascular diseases, chronic lung disease, diabetes) and need for frequent hospitalizations and visits. A series of observational studies demonstrated that cancer patients infected with COVID-19, particularly with lung cancer, have a high rate of morbidity and mortality. Methods: We conducted a review of several observational studies and guidelines regarding the management of cancer patients in the context of COVID-19 infection. Conclusions: The oncologists, according to the main available recommendations, should carefully weigh risks/benefits when planning therapies and follow-up visits. They should defeat the “distraction effect” of the pandemic, which is represented by the risk of shifting attention away from standard therapeutic approach to COVID-19 only. In addition, health authorities should prioritize COVID-19 vaccinations for cancer patients with the aim of limiting the consequences of the pandemic in this particularly frail population.